ANALISIS YURIDIS FUNGSI OTORITAS JASA KEUANGAN (OJK) SEBAGAI PELINDUNG NASABAH PERUSAHAAN ASURANSI - Dede Aquari Irawan Surbakti; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (USU LAW JOURNAL, 2017)
ABSTRACT Regulation on consumer protection in Indonesia has especially existed since Law No. 8/1999 on Consumer Protection was in effect. In its development, consumer protection in also done by independent institutions, based on Law No. 21/2011 which is called OJK which functions to organize an integrated regulation and supervision system toward all activities in financial service sector. One of the goals of establishment o OJK is to protect consumers and society. In order to achieve that goal, OJK issued POJK No. 01/POJK.07/2013 on Customer Protection in Financial Service Sector. One of the financial service sectors supervised by OJK is insurance system. Today, insurance is regulated in Law No.40/2014. The research problems are as follows: how about the role of OJK in protecting insurance company customers in the insurance legl system in Indonesia,how about the difference between consumer protection, stipulated in Law No 8/1999 on Customer Protection, and that which is regulated in Law No. 21/2011 on OJK in conjuction with POJK No. 01/POJK/07/2013 on Customer Protection in Financial Service Sector. The research used judicial normative and descriptive analytic method. The theory used in this research was analytical legal positivism theory ad theary of legal protection. The data were obtained from primary, secondary, and tertiary legal materials and supported by legal provision approach. The result of the research showed that,first,after  Law No.40/2014 on Insurance was in effect, the role of OJK was very strategic as an institution which regulates and supervises insurance companies since they request license for the establishment. It also has the right to impose severe administrative sanction by revoking insurance company which is potential to harm their consumers. Secondly, in providing legal protection for insurance customers, OJK, through POJK No. 01/POJK.07/2013 provides more maximal legal protection than Law No 8/1999 on Consumer Protection. Keywords:                OJK (Financial Service Authority),Insurance Customers,Consumer protection